The Chemical Characteristics of Iron Oxide/Carbon Synthesized by the Arc Discharge Method in Liquid Media with the Addition of Ammonia - Indah Retnosari; Ikrima Nur Hayati; Amalia Amalia; Sri Hastuti; Teguh Endah Saraswati (Jurnal Kimia Sains dan Aplikasi, 2018)
The chemical characteristics of composite material of iron oxide with carbon synthesized by arc discharge method in liquid medium have been identified. The liquid medium used in the method was ethanol with ammonia addition. The chemical characteristics of the resulting product were studied by Fourier transform infrared spectroscopy (FTIR) and energy dispersive X-ray (EDX). The morphology of the material was studied by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The observed materials have a spherical and orderly structure. The FTIR spectra profile shows the peaks of N-H and C-N. The amino groups coming from ammonia as a liquid medium during arc discharge were supposed to have been covalently attached to carbon materials composited with iron oxide. The elemental analysis of EDX confirms the presence of nitrogen elements that were not found on the materials synthesized in arc discharge without ammonia addition.